Developing English Grammar Instructional Materials Oriented to Constructivism Theory - Andika, Andika; Tahrun, Tahrun; Firdaus, Masagus (Universitas Pendidikan Mandalika, 2023)
The enhancement or modification of instructional materials is essential to ensure their effectiveness as teaching aids. For the purpose of improving the quality of instructional materials and making them more appealing to educators and students alike, a comprehensive approach must be taken that considers both the content and the form of the materials. In order to make the module an attractive teaching material, it is imperative to enhance its quality. This study aimed to identify the optimal approach for developing an English grammar instructional material based on the constructivist theory and to assess its validity. The research employed a research and development method using the DDR model. The study findings reveal that the English grammar subject 1 module, containing basic and simple materials, is the most suitable form for developing an instructional material oriented to constructivism theory. Additionally, the presentation of the module is clear and well-organized, the language used is easily comprehensible, and the module's structure is user-friendly and engaging. Furthermore, the validation results demonstrate that the developed module is highly effective as an instructional material for teaching English grammar, attesting to its overall quality.